Epimedin B exhibits pigmentation by increasing tyrosinase family proteins expression, activity, and stability - Chen Hong; Yifan Zhang; Lili Yang; Haoyang Xu; Kang Cheng; Zhi Lv; Kaixian Chen; Yiming Li; Huali Wu (Elsevier, 2024)
Epimedin B (EB) is one of the main flavonoid ingredients present in Epimedium brevicornum Maxim., a traditional herb widely used in China. Our previous study showed that EB was a stronger inducer of melanogenesis and an activator of tyrosinase (TYR). However, the role of EB in melanogenesis and the mechanism underlying the regulation remain unclear. Herein, as an extension to our previous investigation, we provide comprehensive evidence of EB-induced pigmentation in vivo and in vitro and elucidate the melanogenesis mechanism by assessing its effects on the TYR family of proteins (TYRs) in terms of expression, activity, and stability. The results showed that EB increased TYRs expression through microphthalmia-associated transcription factor-mediated p-Akt (referred to as protein kinase B (PKB))/glycogen synthase kinase 3β (GSK3β)/β-catenin, p-p70 S6 kinase cascades, and protein 38 (p38)/mitogen-activated protein (MAP) kinase (MAPK) and extracellular regulated protein kinases (ERK)/MAPK pathways, after which EB increased the number of melanosomes and promoted their maturation for melanogenesis in melanoma cells and human primary melanocytes/skin tissues. Furthermore, EB exerted repigmentation by stimulating TYR activity in hydroquinone- and N-phenylthiourea-induced TYR inhibitive models, including melanoma cells, zebrafish, and mice. Finally, EB ameliorated monobenzone-induced depigmentation in vitro and in vivo through the enhancement of TYRs stability by inhibiting TYR misfolding, TYR-related protein 1 formation, and retention in the endoplasmic reticulum and then by downregulating the ubiquitination and proteolysis processes. These data conclude that EB can target TYRs and alter their expression, activity, and stability, thus stimulating their pigmentation function, which might provide a novel rational strategy for hypopigmentation treatment in the pharmaceutical and cosmetic industries.